A case report of a hemorrhagic stroke with right hemiparesis - Franklin Baltodano Ardón; Indira Pineda Grillo; Shirley Mireya Ortiz Pérez; David Marcelo Guevara Hernández (Medičnì Perspektivi, 2025)
Cardiovascular diseases and dyslipidemia lead to complications such as cerebrovascular accidents and severe sequelae such as neurological deficits in different presentations depending on the affected area. The objective is to describe the clinical case of a patient with hemorrhagic cerebrovascular disease, presenting with right-sided hemiparesis and ataxia, as well as the therapeutic options employed in their rehabilitation process to improve their quality of life. The present investigation deals with a case report that provides relevant information before the implementation of a personalized interdisciplinary treatment, corresponding to a 53-year-old male patient with a history of hypertension and dyslipidemia. Outcome – the case reflects a patient with a neurological condition presenting challenges in communication and mobility, requiring a comprehensive approach to treatment and follow-up to address both acute symptoms and possible underlying impairments. The emergent approach in patients with stroke is determinant to reduce possible sequelae, a personalized comprehensive care involving an interdisciplinary team is essential to improve the prognosis on the patient's quality of life and functionality.